Laser etching ABS (Acrylonitrile Butadiene Styrene) resin composition as well as preparation method and application thereof

By using thermally conductive ceramic powder and radially conductive additives in the laser marking ABS resin composition, the problem of poor heat derivation during laser marking is solved, the production efficiency and material clarity are improved, and it is suitable for a variety of application fields.

CN119752090AActive Publication Date: 2025-04-04SHANGHAI CHUANGYUAN COSMETICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411600509.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-04-04
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing radium engraving masterbatch cannot effectively deduce the heat in the matrix resin during laser marking, resulting in ablation, foaming and coking problems, affecting the production efficiency of radium engraving and the surface clarity of the material.

Method used

By using thermally conductive ceramic powder and radially conductive additives in the ABS resin composition, the heat dissipation effect of the matrix resin is improved and problems such as ablation, foaming and coking are solved.

Benefits of technology

It significantly improves the production efficiency of radium engraving, improves the clarity of radium engraving text or images on the surface of the material, and is widely used in cosmetic container packaging, household electronics and office supplies and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128178270000111
    Figure BDA0005128178270000111
  • Figure BDA0005128178270000121
    Figure BDA0005128178270000121
Patent Text Reader

Abstract

The invention discloses a laser etching ABS (Acrylonitrile Butadiene Styrene) resin composition which comprises the following raw material components in parts by weight: 10-60 parts of ABS resin; 1-20 parts of a laser etching auxiliary agent; 1-30 parts of heat-conducting ceramic powder; 1-30 parts of an inorganic filler; and 0.1 to 10 parts of toner. Through synergistic compounding use of the heat-conducting ceramic powder and the laser etching auxiliary agent in the system, the heat dissipation effect of the matrix resin is greatly improved, and the problems of ablation, foaming, coking and the like in the resin laser etching process are solved, so that the effects of improving the laser etching production efficiency and improving the definition of laser etching characters or images on the surface of a material are achieved. In addition, the invention also provides a preparation process of the laser etching ABS resin composition and application of the laser etching ABS resin composition in laser marking in the fields of cosmetic container packaging, household electronics, office supplies and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a laser-engraved ABS resin composition and a preparation method and application thereof. Background Art

[0002] Laser marking technology is an industrial marking method that has developed rapidly in recent years. Compared with traditional marking methods (mechanical engraving, chemical corrosion, screen printing, ink printing, etc.), laser marking has obvious advantages: 1. Wide range of applications: It can mark almost all materials. 2. High marking efficiency: The laser beam under computer control can move at high speed, and the usual marking process can be completed within seconds, which can realize online marking. 3. High marking accuracy: The laser can form an extremely fine beam, and the thinnest line width on the surface of the material can reach the micron level, which can print various graphics, trademarks, barcodes, and two-dimensional codes. 4. Low cost of use: Laser marking is a non-contact marking, which is not limited by the fatigue service life of the usual mold marking, and the maintenance cost in batch processing is extremely low. At present, in the marking and printing industry, laser marking has occupied more than 90% of the market. Laser marking can be applied to a variety of materials including plastics, rubber, metals, silicon wafers, etc.

[0003] The basic principle of laser marking is that a high-energy continuous laser beam is generated by a laser generator. When the laser acts on the printing material, the atoms in the ground state transition to a higher energy state. The atoms in the higher energy state are unstable and will quickly return to the ground state. When the atoms return to the ground state, they will release additional energy in the form of photons or quanta, and convert the light energy into heat energy, causing the surface material to melt instantly or even vaporize, thereby forming a graphic mark.

[0004] The patent with application number 201710488854.2 discloses a laser engraving masterbatch, which uses polypropylene as a masterbatch carrier and includes inorganic oxides accounting for 15-25% of the total weight by weight of the raw materials. A laser-markable high-flow high-gloss black polypropylene composition is also disclosed, which includes the following components by weight of raw materials: 1-5 parts of laser engraving masterbatch, 71.4-90.4 parts of polypropylene resin, 2-5 parts of C5 petroleum resin, 5-15 parts of barium sulfate, 0.1-0.4 parts of nucleating agent, 0.2-0.6 parts of antioxidant, 1-2 parts of color powder, and 0.3-0.6 parts of lubricant. The laser engraving masterbatch in this patent is mixed with inorganic oxides by photosensitizer, thereby greatly improving the clarity of laser marking and the whiteness of the marked text after the laser engraving masterbatch is used as an effective ingredient in the laser-markable polypropylene composition. The laser-markable polypropylene composition in the patent has high fluidity, high brightness blackness, high whiteness and high definition of the laser mark, ensuring that the appearance of the product after laser marking is not easily damaged. The composition has a good application prospect in the housing of household appliances.

[0005] Patent No. 201410837554.7 discloses a laser engraving masterbatch for light-colored marking, its preparation method and application. The masterbatch includes the following components in parts by weight: 95-66 parts of carrier resin; 0.01-0.5 parts of light-absorbing color powder; 0.01-0.5 parts of light-reflecting powder; 0.7-6 parts of foaming agent; 0.05-1.5 parts of carbon black; 5-20 parts of whitening filler; 0.01-4 parts of processing modified oil. The laser engraving masterbatch in this patent has good compatibility and uniform dispersion in the matrix resin because the carrier resin in the masterbatch can be selected according to the applied matrix resin. A small amount of addition can have both engraving and foaming effects under the action of laser, and can be applied to different matrix resins. The marking effect is uniform, clear, and has a high contrast with the resin, and the mechanical properties of the original resin material are maintained unaffected. It can be used in the field of laser marking modified plastics and is widely used in various general plastics and engineering plastics.

[0006] However, the laser engraving masterbatch prepared by the above patent cannot effectively remove the heat in the matrix resin during the laser marking process when it is used in specific applications, and cannot effectively solve the problems of ablation, foaming, and coking during the laser etching resin process. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a laser engraving ABS resin composition, which greatly improves the heat dissipation effect of the matrix resin by synergistically compounding the thermal conductive ceramic powder and the laser engraving auxiliary agent in the system, solves the problems of ablation, foaming, coking, etc. in the laser etching resin process, thereby achieving the effect of improving the laser engraving production efficiency and improving the clarity of the laser engraved text or image on the material surface. In addition, the present invention also provides a preparation process of the above-mentioned laser engraving ABS resin composition and its application in the fields of cosmetic container packaging, household electronics, office supplies, etc. for laser marking.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] In a first aspect of the present invention, a laser-engraved ABS resin composition is provided, comprising the following raw material components in parts by weight:

[0010] ABS resin 10-60 parts;

[0011] 1 to 20 parts of laser engraving additives;

[0012] 1 to 30 parts of thermal conductive ceramic powder;

[0013] 1 to 30 parts of inorganic filler;

[0014] Color powder 0.1 to 10 parts.

[0015] Preferably, the raw material components include the following parts by weight:

[0016] ABS resin 15-40 parts;

[0017] 5-15 parts of laser engraving additives;

[0018] 5-30 parts of thermal conductive ceramic powder;

[0019] 5-25 parts of inorganic filler;

[0020] 0.5 to 5 parts of color powder.

[0021] Furthermore, the thermally conductive ceramic powder is a mixture of one or more of aluminum nitride, boron nitride and silicon nitride.

[0022] When the thermally conductive ceramic powder adopts a single component, the experimental results show that the product system has the best effect when aluminum nitride is selected, and aluminum nitride with an average particle size of ≤50μm is preferred.

[0023] Preferably, the thermally conductive ceramic powder is a mixture of aluminum nitride and boron nitride and / or silicon nitride.

[0024] The experimental results show that compared with a single component of thermally conductive ceramic powder, the use of multiple ceramic powder components in combination can achieve better results. Specifically, the thermally conductive ceramic powder can be a mixture of aluminum nitride and boron nitride, or aluminum nitride and silicon nitride.

[0025] Furthermore, the laser engraving auxiliary agent is titanium dioxide.

[0026] Furthermore, it also includes 0-10 parts of elastomer, 0-1 part of antioxidant, and 0-1 part of coupling agent.

[0027] Preferably, 0.5 to 5 parts of elastomer, 0.1 to 1 parts of antioxidant, and 0.1 to 1 parts of coupling agent are added to the system.

[0028] Specifically, the inorganic filler may be calcium carbonate, talcum powder, mica powder, quartz powder, etc. The color powder may be carbon black, iron oxide series pigments, cobalt blue, bismuth yellow, etc. The elastomer may be styrene elastomer TPS, olefin elastomer TPO, polyurethane elastomer TPU, polyester elastomer TPEE, etc. The antioxidant may be antioxidant 1010 and / or antioxidant 168. The coupling agent may be silane coupling agent, titanate coupling agent, aluminate coupling agent, borate coupling agent, etc.

[0029] The second aspect of the present invention provides a method for preparing the above-mentioned laser-engraved ABS resin composition, comprising the following steps:

[0030] S1, adding each raw material component into a high-speed mixer in sequence and mixing them evenly to obtain a mixed material;

[0031] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a laser-carved ABS resin composition masterbatch;

[0032] Wherein, in step S2, the melting temperature is 180-260°C, and the screw speed is 200-600 rpm.

[0033] Furthermore, in step S2, the melting temperature is 200-240° C., and the screw speed is 300-500 rpm.

[0034] A third aspect of the present invention provides an application of the above-mentioned laser-engraved ABS resin composition, wherein the laser-engraved ABS resin composition is added to a base resin and applied to the field of laser marking cosmetic container packaging, household electronics or office supplies.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The present invention uses a synergistic combination of thermally conductive ceramic powder and laser engraving additives in the product system to greatly improve the heat dissipation effect of the matrix resin, solve the problems of ablation, foaming, and coking in the laser etching resin process, thereby achieving the effect of improving the laser engraving production efficiency and improving the clarity of laser engraved text or images on the material surface. The laser engraving ABS resin composition can be widely used in the fields of cosmetic container packaging, household electronics, office supplies, etc. DETAILED DESCRIPTION

[0037] The technical solutions in the present invention will be described clearly and completely below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0040] ABS resin 35 parts;

[0041] 5 parts of laser engraving additives;

[0042] Thermally conductive ceramic powder 10 parts;

[0043] 10 parts of inorganic filler;

[0044] 1 part of color powder;

[0045] 1 part of elastomer;

[0046] 1 part antioxidant;

[0047] 1 part of coupling agent.

[0048] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is aluminum nitride, whose thermal conductivity is 200W / (m·K) and the average particle size is 30μm; the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0049] The preparation method of the laser-engraved ABS resin composition in this embodiment is as follows:

[0050] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 300 rpm for 5 minutes to obtain a mixed material;

[0051] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a laser-carved ABS resin composition masterbatch;

[0052] Wherein, in step S2, the melting temperature is 220°C and the screw speed is 400 rpm.

[0053] Example 2

[0054] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0055] ABS resin 35 parts;

[0056] 5 parts of laser engraving additives;

[0057] Thermally conductive ceramic powder 10 parts;

[0058] 10 parts of inorganic filler;

[0059] 1 part of color powder;

[0060] 1 part of elastomer;

[0061] 1 part antioxidant;

[0062] 1 part of coupling agent.

[0063] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is aluminum nitride, whose thermal conductivity is 200W / (m·K) and the average particle size is 100μm; the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0064] The preparation method of the laser-engraved ABS resin composition in this embodiment is the same as that in Example 1.

[0065] Example 3

[0066] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0067] ABS resin 35 parts;

[0068] 5 parts of laser engraving additives;

[0069] Thermally conductive ceramic powder 10 parts;

[0070] 10 parts of inorganic filler;

[0071] 1 part of color powder;

[0072] 1 part of elastomer;

[0073] 1 part antioxidant;

[0074] 1 part of coupling agent.

[0075] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is boron nitride, and its thermal conductivity is 57W / (m·K); the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0076] The preparation method of the laser-engraved ABS resin composition in this embodiment is the same as that in Example 1.

[0077] Example 4

[0078] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0079] ABS resin 35 parts;

[0080] 5 parts of laser engraving additives;

[0081] Thermally conductive ceramic powder 10 parts;

[0082] 10 parts of inorganic filler;

[0083] 1 part of color powder;

[0084] 1 part of elastomer;

[0085] 1 part antioxidant;

[0086] 1 part of coupling agent.

[0087] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is silicon nitride, and its thermal conductivity is 21W / (m·K); the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0088] The preparation method of the laser-engraved ABS resin composition in this embodiment is the same as that in Example 1.

[0089] Example 5

[0090] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0091] ABS resin 35 parts;

[0092] 5 parts of laser engraving additives;

[0093] 20 parts of thermal conductive ceramic powder;

[0094] 10 parts of inorganic filler;

[0095] 1 part of color powder;

[0096] 1 part of elastomer;

[0097] 1 part antioxidant;

[0098] 1 part of coupling agent.

[0099] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is 10 parts of aluminum nitride and 10 parts of silicon nitride, the thermal conductivity of aluminum nitride is 200W / (m·K), the average particle size is 30μm, and the thermal conductivity of silicon nitride is 21W / (m·K); the inorganic filler is mica; the color powder is carbon black; the elastomer is an olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; the coupling agent is KH560.

[0100] The preparation method of the laser-engraved ABS resin composition in this embodiment is the same as that in Example 1.

[0101] Example 6

[0102] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0103] ABS resin 35 parts;

[0104] 5 parts of laser engraving additives;

[0105] 20 parts of thermal conductive ceramic powder;

[0106] 10 parts of inorganic filler;

[0107] 1 part of color powder;

[0108] 1 part of elastomer;

[0109] 1 part antioxidant;

[0110] 1 part of coupling agent.

[0111] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is 10 parts of aluminum nitride and 10 parts of boron nitride, the thermal conductivity of aluminum nitride is 200W / (m·K), the average particle size is 30μm, and the thermal conductivity of boron nitride is 57W / (m·K); the inorganic filler is mica; the color powder is carbon black; the elastomer is an olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; the coupling agent is KH560.

[0112] The preparation method of the laser-engraved ABS resin composition in this embodiment is the same as that in Example 1.

[0113] Example 7

[0114] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0115] ABS resin 35 parts;

[0116] 5 parts of laser engraving additives;

[0117] 25 parts of thermal conductive ceramic powder;

[0118] 10 parts of inorganic filler;

[0119] 1 part of color powder;

[0120] 1 part of elastomer;

[0121] 1 part antioxidant;

[0122] 1 part of coupling agent.

[0123] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is 15 parts of aluminum nitride and 10 parts of silicon nitride, the thermal conductivity of aluminum nitride is 200W / (m·K), the average particle size is 30μm, and the thermal conductivity of silicon nitride is 21W / (m·K); the inorganic filler is mica; the color powder is carbon black; the elastomer is an olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; the coupling agent is KH560.

[0124] The preparation method of the laser-engraved ABS resin composition in this embodiment is the same as that in Example 1.

[0125] Comparative Example 1

[0126] The laser engraving ABS resin composition in this comparative example includes the following raw material components in parts by weight:

[0127] ABS resin 35 parts;

[0128] 5 parts of laser engraving additives;

[0129] 35 parts of thermal conductive ceramic powder;

[0130] 10 parts of inorganic filler;

[0131] 1 part of color powder;

[0132] 1 part of elastomer;

[0133] 1 part antioxidant;

[0134] 1 part of coupling agent.

[0135] Among them, the laser carving additive is titanium dioxide; the thermal conductive ceramic powder is 25 parts of aluminum nitride and 10 parts of silicon nitride, the thermal conductivity of aluminum nitride is 200W / (m·K), the average particle size is 30μm, and the thermal conductivity of silicon nitride is 21W / (m·K); the inorganic filler is mica; the color powder is carbon black; the elastomer is an olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; the coupling agent is KH560.

[0136] The preparation method of the laser-engraved ABS resin composition in this comparative example is the same as that in Example 1.

[0137] Comparative Example 2

[0138] Comparative Example 2 is a comparative experimental example of Example 1, and the difference between Comparative Example 2 and Example 1 is that no thermal conductive ceramic powder is added to the product system.

[0139] The laser engraving ABS resin composition of this comparative example comprises the following raw material components in parts by weight:

[0140] ABS resin 35 parts;

[0141] 5 parts of laser engraving additives;

[0142] 10 parts of inorganic filler;

[0143] 1 part of color powder;

[0144] 1 part of elastomer;

[0145] 1 part antioxidant;

[0146] 1 part of coupling agent.

[0147] Among them, the laser carving additive is titanium dioxide; the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0148] The preparation method of the laser-engraved ABS resin composition in this comparative example is the same as that in Example 1.

[0149] Comparative Example 3

[0150] Comparative Example 3 is a comparative experimental example of Example 1, and the difference between Comparative Example 3 and Example 1 is that no laser engraving auxiliary agent is added to the product system.

[0151] The laser engraving ABS resin composition in this comparative example includes the following raw material components in parts by weight:

[0152] ABS resin 35 parts;

[0153] Thermally conductive ceramic powder 10 parts;

[0154] 10 parts of inorganic filler;

[0155] 1 part of color powder;

[0156] 1 part of elastomer;

[0157] 1 part antioxidant;

[0158] 1 part of coupling agent.

[0159] Among them, the thermal conductive ceramic powder is aluminum nitride, the thermal conductivity of aluminum nitride is 200W / (m·K), and the average particle size is 30μm; the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0160] The preparation method of the laser-engraved ABS resin composition in this comparative example is the same as that in Example 1.

[0161] Example 8

[0162] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0163] ABS resin 10 parts;

[0164] 1 part of laser engraving additive;

[0165] 1 part thermal conductive ceramic powder;

[0166] 1 part of inorganic filler;

[0167] Color powder 0.1 part;

[0168] 0.5 parts of elastomer;

[0169] Antioxidant 0.1 part;

[0170] 0.1 part of coupling agent.

[0171] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is aluminum nitride, whose thermal conductivity is 200W / (m·K) and the average particle size is 30μm; the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0172] The preparation method of the laser-engraved ABS resin composition in this embodiment is as follows:

[0173] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 1 minute, and stir at a high speed of 300 rpm for 2 minutes to obtain a mixed material;

[0174] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a laser-carved ABS resin composition masterbatch;

[0175] Wherein, in step S2, the melting temperature is 180°C and the screw speed is 200 rpm.

[0176] Example 9

[0177] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0178] ABS resin 15 parts;

[0179] 2 parts of laser engraving additive;

[0180] 5 parts of thermal conductive ceramic powder;

[0181] 5 parts of inorganic filler;

[0182] 0.5 parts of color powder;

[0183] 5 parts of elastomer;

[0184] 0.5 parts of antioxidant;

[0185] 0.5 parts of coupling agent.

[0186] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is aluminum nitride, whose thermal conductivity is 200W / (m·K) and the average particle size is 30μm; the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0187] The preparation method of the laser-engraved ABS resin composition in this embodiment is as follows:

[0188] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 300 rpm for 4 minutes to obtain a mixed material;

[0189] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a laser-carved ABS resin composition masterbatch;

[0190] Wherein, in step S2, the melting temperature is 200°C and the screw speed is 300 rpm.

[0191] Example 10

[0192] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0193] ABS resin 40 parts;

[0194] 15 parts of laser engraving additives;

[0195] Thermally conductive ceramic powder 10 parts;

[0196] 25 parts of inorganic filler;

[0197] 5 parts of color powder;

[0198] 5 parts of elastomer;

[0199] 1 part antioxidant;

[0200] 1 part of coupling agent.

[0201] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is aluminum nitride, whose thermal conductivity is 200W / (m·K) and the average particle size is 30μm; the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0202] The preparation method of the laser-engraved ABS resin composition in this embodiment is as follows:

[0203] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 300 rpm for 5 minutes to obtain a mixed material;

[0204] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a laser-carved ABS resin composition masterbatch;

[0205] Wherein, in step S2, the melting temperature is 240°C and the screw speed is 400 rpm.

[0206] Embodiment 11

[0207] The laser engraving ABS resin composition in this embodiment includes the following raw material components in parts by weight:

[0208] ABS resin 60 parts;

[0209] 20 parts of laser engraving additives;

[0210] 30 parts of thermal conductive ceramic powder;

[0211] 30 parts of inorganic filler;

[0212] Color powder 10 parts;

[0213] Elastomer 10 parts;

[0214] 1 part antioxidant;

[0215] 1 part of coupling agent.

[0216] Among them, the laser engraving additive is titanium dioxide; the thermal conductive ceramic powder is aluminum nitride, whose thermal conductivity is 200W / (m·K) and the average particle size is 30μm; the inorganic filler is mica; the color powder is carbon black; the elastomer is olefin elastomer TPO; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a dosage ratio of 1:1; and the coupling agent is KH560.

[0217] The preparation method of the laser-engraved ABS resin composition in this embodiment is as follows:

[0218] S1. Add each raw material component into a high-speed mixer in sequence, stir at a low speed of 50 rpm for 2 minutes, and stir at a high speed of 300 rpm for 5 minutes to obtain a mixed material;

[0219] S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a laser-carved ABS resin composition masterbatch;

[0220] Wherein, in step S2, the melting temperature is 260°C and the screw speed is 600 rpm.

[0221] The laser-carved ABS resin composition masterbatches prepared in Examples 1 to 11 and Comparative Examples 1 to 3 were respectively applied to the ABS resin matrix. The specific product formula is as follows: 3 parts of the laser-carved ABS resin composition masterbatch and 100 parts of ABS resin.

[0222] The preparation process is as follows:

[0223] (1) adding ABS resin and laser-engraved ABS resin composition masterbatch into a high-speed mixer and mixing them evenly to obtain a mixed material;

[0224] (2) The mixed material is added into a twin-screw extruder with a screw speed of 400 rpm and a temperature of 250°C. Under the conveying and shearing action of the twin-screw extruder, the mixed material is fully melted and plasticized, kneaded and mixed, extruded through a die, drawn into strips, cooled, pelletized, dried, and finally packaged to obtain a laser-engraved ABS resin material.

[0225] The performance test of the laser-engraved ABS resin material prepared above is carried out. The test results are shown in Table 1. The test standards are as follows:

[0226] Flexural strength is tested according to ISO 527, flexural modulus is tested according to ISO 178, tensile strength is tested according to ISO 178, and impact strength (unnotched) is tested according to ISO 180.

[0227] The laser marking equipment used is ZX-20F (Shanghai Zhengxuan Laser Equipment Co., Ltd.) model laser marking equipment, with a laser wavelength of 1064nm nm and a laser power of 700w.

[0228] The clarity of the laser printed mark is evaluated by visual inspection, and the clarity is marked as 1, 2, 3, 4, 5, and 6 from low to high. A colorimeter is used to test the blackness value of the laser marking area, and a gloss tester ASTM G272-19 is used to test the gloss of the product.

[0229] Table 1

[0230]

[0231]

[0232] It can be seen from the test results in Table 1 that, by comparing Examples 1-4, different types of thermally conductive ceramic powders are used in the product systems. Due to the difference in thermal conductivity, the overall performance of the product is optimal when aluminum nitride is used as the thermally conductive ceramic powder, and the average particle size of aluminum nitride is preferably ≤50 μm.

[0233] Comparing Examples 1, 5, and 6, the difference between the three is that in Example 1, aluminum nitride is used as the thermally conductive ceramic powder, and in Examples 5 and 6, two thermally conductive ceramic powders are mixed, wherein in Example 5, a compound of aluminum nitride and silicon nitride is used as the thermally conductive ceramic powder, and in Example 6, a compound of aluminum nitride and boron nitride is used as the thermally conductive ceramic powder. After testing, the overall performance of the products obtained in Examples 5 and 6 is better than that in Example 1, indicating that mixing multiple thermally conductive ceramic powders has a better effect.

[0234] Comparing Examples 5 and 7 with Comparative Example 1, the difference between the three is that the amount of thermally conductive ceramic powder in the system is different. The amount of thermally conductive ceramic powder in Example 5 is 20 parts by weight, the amount of thermally conductive ceramic powder in Example 7 is 25 parts by weight, and the amount of thermally conductive ceramic powder in Comparative Example 1 is 35 parts by weight. The overall performance of the product prepared in Example 7 is better, and the overall performance of the product prepared in Comparative Example 1 is the worst, indicating that the amount of thermally conductive ceramic powder in the product system of the present invention is preferably 5 to 30 parts by weight, and more preferably 25 parts by weight.

[0235] Comparing Example 1 with Comparative Examples 2 and 3, the difference between the three is that in Example 1, laser engraving aid titanium dioxide and thermal conductive ceramic powder aluminum nitride are compounded, in Comparative Example 2, only laser engraving aid titanium dioxide is added without thermal conductive ceramic powder, and in Comparative Example 3, only thermal conductive ceramic powder is added without laser engraving aid titanium dioxide. After testing, the performance of the products obtained in Comparative Examples 2 and 3 is obviously poor, indicating that the compound use of thermal conductive ceramic powder and laser engraving aid in the product system plays a synergistic role.

[0236] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A laser engraved ABS resin composition, characterized in that: The invention comprises the following raw material components in parts by weight: ABS resin 10-60 parts; 1 to 20 parts of laser engraving additives; 1 to 30 parts of thermal conductive ceramic powder; 1 to 30 parts of inorganic filler; Color powder 0.1 to 10 parts.

2. The laser engraving ABS resin composition according to claim 1, characterized in that: The invention comprises the following raw material components in parts by weight: ABS resin 15-40 parts; 5-15 parts of laser engraving additives; 5-30 parts of thermal conductive ceramic powder; 5-25 parts of inorganic filler; 0.5 to 5 parts of color powder.

3. The laser engraving ABS resin composition according to claim 2, characterized in that: The thermally conductive ceramic powder is a mixture of one or more of aluminum nitride, boron nitride and silicon nitride.

4. The laser engraving ABS resin composition according to claim 3, characterized in that: The thermally conductive ceramic powder is a mixture of aluminum nitride and boron nitride and / or silicon nitride.

5. The laser engraving ABS resin composition according to claim 4, characterized in that: The average particle size of the aluminum nitride is ≤50 μm.

6. The laser engraving ABS resin composition according to claim 1, characterized in that: The laser engraving auxiliary agent is titanium dioxide.

7. The laser engraving ABS resin composition according to claim 1, characterized in that: It also includes 0-10 parts of elastomer, 0-1 parts of antioxidant and 0-1 parts of coupling agent.

8. A method for preparing a laser-engraved ABS resin composition as claimed in any one of claims 1 to 7, characterized in that: The steps include: S1, adding each raw material component into a high-speed mixer in sequence and mixing them evenly to obtain a mixed material; S2, adding the mixed material into a twin-screw extruder, and performing melt blending and extrusion granulation to obtain a laser-carved ABS resin composition masterbatch; Wherein, in step S2, the melting temperature is 180-260°C, and the screw speed is 200-600 rpm.

9. The method for preparing the laser-engraved ABS resin composition according to claim 8, characterized in that: In the step S2, the melting temperature is 200-240°C, and the screw speed is 300-500 rpm.

10. An application of the laser engraving ABS resin composition according to any one of claims 1 to 7, characterized in that: The laser-engraved ABS resin composition is added to a base resin and is applied to the fields of laser marking cosmetic container packaging, household electronics or office supplies.

Citation Information

Patent Citations

  • ABS plastic for enhancing laser marking effect and preparation method thereof

    CN101143958A

  • Laser etching master batch for light color identification, preparation method thereof and application

    CN104448531A

  • Compound capable of realizing low-temperature laser etching of multiple colors and preparation method thereof

    CN110511526A

  • Polyamide composite material capable of being subjected to laser etching and preparation method of polyamide composite material

    CN113736247A

  • Laser direct structuring resin with improved heat dissipation performance

    KR101940030B1